BIM Performance, Project Complexity, and User Satisfaction: A QCA Study of 39 Cases - Hui-jie Jiang; Zhi-peng Cui; Hang Yin; Zhong-bao Yang (Advances in Civil Engineering)
Although the realization of building information modeling (BIM) performance is the basis for the generation of user’s satisfaction, few studies have explored the influence path between BIM performance and BIM user’s satisfaction in recent years. Therefore, to enrich the research results of BIM user’s satisfaction and provide reference schemes for engineering practice, this study adopts the fsQCA (fuzzy-set qualitative comparative analysis) method, taking 39 project cases using BIM technology as the base sample to analyze the influence path between BIM performance and user’s satisfaction. Moreover, this study is based on the configuration theory, examining four elements of BIM performance: BIM accuracy, information integration, functional advantages and manager support, and the complexity of the project. Finally, this study identifies three types of configuration results: performance type, support type, and comprehensive type. The performance type can achieve high user satisfaction in relatively complex projects; the support type requires executive support to improve user satisfaction in less complex projects, and the comprehensive type improves satisfaction through multiple BIM performances without considering project complexity.